Application of the 6S management strategies - Haiying Deng; Lizhen Lin (Wiley, 2023)
Abstract Aim To explore the value of the 6S management strategies in COVID‐19 wards. Design Nurses from the first Fujian medical team in aiding Hubei Province at Wuhan Jinyintan Hospital (2 February, 2020-24 March, 2020) were recruited and instructed to adopt the 6S management strategies for nursing management. Methods The paired‐sample t‐test was performed to compare the nursing quality, core capabilities of nurses, nursing preparation time, and nursing error rates before and after implementation. Results After implementation of the 6S management strategies, a total of 93 nurses experienced significant improvements in nursing quality, especially in workplace stress, material preparation, and medication management (p < .001). Adoption of the 6S model for nursing management in COVID‐19 wards effectively improves nursing quality, enhances the core capabilities of nurses, reduces nursing preparation time, and lowers nursing error rates.